Kemampuan Komunikasi Interpersonal Guru Dengan Siswa Dalam Pembelajaran IPS Di SMP 21 Kota Bengkulu - Lidya Asmara; Suharmi Suharmi; Herwan MDK (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the interpersonal communication skills of teachers and students in the social studies learning process at SMPN 21 Bengkulu City. The research method used was quantitative descriptive research with research subjects involving 36 class VIII students. Data collection techniques use observation, questionnaires and documentation. The research results show that the teacher's interpersonal communication skills with students in the learning process are quite good. This can be proven by the results of data analysis, the average calculation obtained is 66. Thus, it can be said that if a teacher is able to carry out good interpersonal communication, the students' communication skills in learning will also be higher, but on the contrary, if the teacher's interpersonal communication skills are still low, students' communication skills will also tend to be low. The conclusion from this research is that the teacher's interpersonal communication skills with class VIII students in the social studies learning process at SMPN 21 Bengkulu City are in the Good category. Research can be a basis for teachers to develop their insight and knowledge to improve students' communication skills in the learning process so that they are more effective.